Pre-hospital delays among patients with acute coronary syndrome in the Russian Federation: a multicentre prospective observational cohort study (the AMIR Study) - Bates, Katie; Schirmer, Henrik; Kontsevaya, Anna; Bobrova, Natalia; Leon, David A.; McKee, Martin (Frontiers in Disaster and Emergency Medicine, 2023)
Objective This study aimed to describe total pre-hospital delays (symptom onset to admission), patient delays (symptom onset to calling for help), and transport delays (calling for help to admission) experienced by patients with acute coronary syndrome (ACS) in Russia and identify factors associated with longer delays. Methods A prospective observational cohort study of ACS patients with myocardial infarction recruited in hospitals providing percutaneous coronary intervention (PCI) and those that do not (non-PCI) in 13 regions and at multiple levels of the health system in Russia. Data were collected on pre-hospital delays between symptom onset and admission to the hospital providing definitive treatment, divided into patient delay (time between symptom onset and calling for help) and transport delay (time between calling for help and admission). Results Of 902 patients, 701 (77.7%) had full data on pre-hospital delays. The median total pre-hospital delay in our study was 5.1 h, the median patient delay was 1.5 h, and the median transport delay was 2.1 h. Patient delays did not differ by age and sex, although having an ST-elevation myocardial infarction (STEMI) and certain symptom presentations, including severe pain, reduced delays. Transport delays were markedly reduced in those transported by emergency medical services (EMS) and taken directly to the hospital of definitive treatment (rather than to one closer but unable to offer PCI). Although transport delays were reduced in those using EMS, just half of the patients using EMS had a transport delay of <2 h (first medical contact to admission). Among all patients taken directly to the hospital by EMS, 70% were STEMI patients. Of these STEMI patients, 78% had a transport delay of 2 h or more. Among these patients, only 16.0% received thrombolysis in the ambulance. As expected, regional differences were apparent with all types of delay, with the greatest variation found in transport delays. Conclusion Delays are currently longer than the European Society of Cardiology guidelines for STEMI patients and other severe cases. Reducing patient delays will reduce overall delays. Transport delays are inevitable in many regions of Russia, but better triage of patients, increased use of EMS, and early thrombolysis in EMS, particularly for STEMI patients facing excessive transport delays, will reduce delays and buy time before PCI.